Mechanisms of bar adjustments in the Jingjiang Reach of the Yangtze River in response to the operation of the Three Gorges Dam - Yang, Xuhai; Sun, Zhaohua; Li, Yitian; Deng, Jinyun; Xiong, Haibin; Li, Dongfeng (Journal of Hydrology, 2022)
Dams alter downstream river flow and sediment regimes, causing significant changes in river morphologies. The middle Yangtze River downstream of the Three Gorges Dam (TGD) has experienced rapid erosion in recent years, and the associated morphodynamic changes have negatively impacted the bank stability, navigation waterways and ecological functioning. Earlier studies have analyzed recent channel adjustments in the Yangtze River; however, our understanding of changes in the bar morphodynamics remains incomplete. In this study, we collected and analyzed flow and sediment data (1991∼2016) and river bathymetry data (1975∼2017) and investigated the mechanisms of bar adjustments along the Jingjiang Reach in the post-TGD period. The results indicate that most steady bars with a higher elevation and better vegetation coverage have experienced lateral erosion, while their elevations have remained stable overall. The unvegetated migrating bars with a lower elevation have experienced severe surficial erosion and area shrinkage. A new assessment method of the dominant discharge range on downstream bars is provided after dam closure. The new dominant discharge range that determines bar adjustments corresponds to the flow stages between the submersion of migrating bars (∼12,500 m3/s) and the overtopping of vegetated steady bars (∼27,500 m3/s) in the Jingjiang Reach. A quantitative relationship exists between bar erosion in response to changed dominant discharge regimes and sediment decline. The significant bar erosion after the operation of the TGD can be attributed to the increased flow duration and the sharp decline in the suspended sediment concentration (SSC) of the dominant discharge range, and changes in SSCs play a primary role. The bar area will decrease by ∼0.003 km2 when the annual cumulative duration of the dominant discharge increases by one day and by ∼0.234 km2 when the annual average SSC of the dominant discharge decreases by 0.01 kg/m3. Furthermore, vegetation encroachment and colonization play a positive role in stabilizing bar morphologies and limiting surficial erosion, whereas vegetation cannot prevent the lateral erosion of steady bars. These findings suggest that multiple controls, including flow, sediment and vegetation, shape the evolution of fluvial bars and have important implications for river management and ecological evaluation in response to the operation of large dams.
Keywords: Bar morphodynamics; Damming; Dominant discharge; Flow-sediment regimes; vegetation